2014
DOI: 10.1021/jf501991q
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Contents, Profiles, and Color Characteristics of Red Cabbage Extracts from Different Cultivars and Maturity Stages

Abstract: Red cabbage (Brassica oleracea L.) is an excellent source of food colorant. This study aimed to evaluate the anthocyanin pigment contents and profiles from seven red cabbage cultivars at two maturity stages (8 weeks apart) and evaluate their color characteristics and behavior under acidic and neutral pH. Anthocyanin concentrations ranged from 1111 to 1780 mg Cy3G/100 g DM and did not increase with time. Cultivar and maturation affected pigment profile. Some varieties accumulated ≥30% of diacylated pigments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 36 publications
9
56
1
1
Order By: Relevance
“…The total monomeric anthocyanin content was quantified using: Total monomeric anthocyanin content0.25em()normalmg0.25emL12em=A×italicMW×italicDF×1000ϵ×l where A = ( A 520 – A 700 ) pH 1.0 – ( A 520 – A 700 ) pH 4.5 , MW is the molecular weight, DF is the dilution factor; l is path length (cm) and ϵ is the molar extinction coefficient. The total anthocyanin content in red cabbage was quantified by considering cyanidin‐3‐glucoside as major anthocyanin, with a molecular weight of 449.2 g mol −1 and a molar extinction coefficient of 26 900 L cm −1 mol −1 …”
Section: Methodsmentioning
confidence: 99%
“…The total monomeric anthocyanin content was quantified using: Total monomeric anthocyanin content0.25em()normalmg0.25emL12em=A×italicMW×italicDF×1000ϵ×l where A = ( A 520 – A 700 ) pH 1.0 – ( A 520 – A 700 ) pH 4.5 , MW is the molecular weight, DF is the dilution factor; l is path length (cm) and ϵ is the molar extinction coefficient. The total anthocyanin content in red cabbage was quantified by considering cyanidin‐3‐glucoside as major anthocyanin, with a molecular weight of 449.2 g mol −1 and a molar extinction coefficient of 26 900 L cm −1 mol −1 …”
Section: Methodsmentioning
confidence: 99%
“…Red cabbage ( Brassica oleracea var. capitata f. rubra) contains a rich source of anthocyanins which can be used as natural food colorants (Ahmadiani, Robbins, Collins, & Giusti, ). However, anthocyanins are relatively susceptible to degradation by pH, temperature, enzymes, oxygen, and light (Jackman, Yada, Tung, & Speers, ).…”
Section: Introductionmentioning
confidence: 99%
“…), a vegetable becoming popular in gourmet circles, can provide a partial solution; the p K a values of its various transitions are shifted a little towards neutrality, increasing the range of food products in which it can be used, making them applicable as neutral pH colorants. It has been demonstrated that red cabbage extracts containing highly acylated anthocyanins can produce blue hues similar to indigo carmine . This increased stability is a result of intramolecular co‐pigmentation effects resulting from acylation of the glycosides with hydroxycinnamic and hydroxybenzoic acids (Figure ) .…”
Section: The Present – Natural Food Colorantsmentioning
confidence: 99%